The foundations of European Union competition law the objective and principles of Article 102 - Nazzini, Renato (Oxford : Oxford University Press, 2011)
Article 82 of the EC Treaty prohibits the abuse of a dominant position as incompatible with the common market. Here the difficulties of assessing abuse in terms of Article 82 in light of the objectives of EU competition law are addressed to establish a robust and workable analytical framework for abuse of dominance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Antitrust law -- European Union countries; Competition, Unfair -- European Union countries